Rekomendasi Lokasi Bisnis UMKM Menggunakan Metode SAW Berbasis WebGIS - Maulana Sidiq, Tubagus Rivan; Karlitasari, Lita; Suriansyah, Muhammad Iqbal (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 10 No 1 (2025): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Juni 2025), 2025)
Determining an ideal business location is a critical factor for small and medium-sized enterprises (SMEs). In order to create a recommendation system based on WebGIS, this study combines the Simple Additive Weighting (SAW) technique with Geographic Information System (GIS) technology. Potential locations in Bogor and Sukabumi were assessed using criteria such as category similarity, regional minimum wages (UMK), and Point of Interest (PoI) density. The system analyzed 10 alternatives by normalizing the data and calculating the rankings based on the SAW method. The results showed that alternatives were ranked according to their total scores, with Cibadak achieving the highest score of 0.775. Consequently, Cibadak is recommended as the most suitable business location. This study lays the groundwork for future advancements in location-based business planning tools and demonstrates how GIS and SAW can enhance SME decision-making processes.